ОСВІТНЬО-ПРОСВІТНИЦЬКА ДІЯЛЬНІСТЬ ПРОЛЕТКУЛЬТУ (1917–1932 рр.) - Кравченко, Оксана (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті висвітлено освітньо-просвітницьку діяльність Пролеткульту (1917–1932 рр.) – культурно-просвітницької і літературно-художньої організації пролетарської самодіяльності при Наркомосі, яка мала за мету широкий і всебічний розвиток пролетарської культури самим пролетаріатом. Основними формами освітньо-просвітницької роботи виступали: робочий клуб, студії (літературні, театральні, музичні, образотворчого мистецтва); пролетарський університет, дитячий Пролеткульт. В статье освещена образовательно-просветительская деятельность Пролеткульта (1917–1932 рр.) – культурно-просветительской и литературно-художественной организации пролетарской самодеятельности при Наркомпросе, которая имела целью широкое и всестороннее развитие пролетарской культуры самым пролетариатом. Основными формами образовательно-просветительской работы выступали: рабочий клуб, студии (литературные, театральные, музыкальные, изобразительного искусства); пролетарский университет, детский Пролеткульт. The article highlights the educational and outreach activities Proletcult (1917–1932) – of cultural and literary and artistic performances in the proletarian organization Commissariat, which had the goal of broad and comprehensive development of proletarian culture by the proletariat. Educational and educational activities aimed at Proletcult comprehensive holistic education of man from preschool to systematically support professional life at work. The main forms of education and educational work were: working club, studies (literature, theater, music, fine arts); proletarian university, children Proletkult. Each form has its own methods, techniques and tools of work. The main shortcomings can distinguish politicization and ideological filling the educational process, the advantage of collectivism over individual creative development, class limitations like. Тhe content of educational and outreach activities Proletcult: learning basic knowledge, education (overall communist wing), development of training and methodological support, training workers Proletcult; skill formation of a new life, antireligious propaganda, literacy, study and work processes of proletarian enterprises; combating and prevention of alcoholism; Legal education workers; physical development; work with women; support children’s movement. The most widespread form of educational outreach Proletcult club was working as a center of educational initiative of the workers. From the very beginning the Proletkult methods laid the foundation of the club, which later gained widespread.